Evaluation of Change Management, Technology Information Systems and K3 Management at PT Trans Jakarta - Rahayu Rahayu; Bambang Fajarisman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Trans Jakarta buses are transportation for the city of Jakarta and its surroundings, Trans Jakarta buses are intended for the people of Jakarta and its surroundings. Trans Jakarta bus operations almost every month have accidents that cause death for the driver and the bus is damaged and the passengers are afraid. The DKI government's policies, which often change due to the pandemic, have an impact on Trans Jakarta's operations. Trans Jakarta's change management is not ready with this policy. The technology and information systems that are running have only reached Trans Jakarta customers, on the other hand, the internal operational management of Trans Jakarta has not maximized the technology and information, as evidenced by the frequent occurrence of Negligence in the field that has not been covered by central management with frequent bus accidents because the driver works more than standard hours. set. To answer the hypothesis, namely the implementation of change management, technology and information systems, and K3 management, the researchers in this study used qualitative research and collected secondary data through literature. The results of this study are implementations that are in accordance with the needs of Trans Jakarta management, namely change management models, technology and information systems models, and K3 management systems.